The Active Fire Protection Prototype for Household-Scale Kitchen Based on Silica Gel from Rice Husk Ash - Sutrsino, Himawan Hadi (International Journal of Integrated Engineering, 2022)
This study aims to create a fire protection design in the kitchen with technology that is easily applied along with inexpensive extinguishing media using silica gel from rice husk ash. By using an experimental method, the active design of fire protection in the kitchen area uses compartmentalization equipped with a gas stove, kitchen equipment, as well as specially designed fire equipment components. The composition of the air in the compartment is calculated based on the volume of the compartment so that it can represent the coverage of oxygen and fuel in accordance with the conditions of free air, while the silica used as an extinguishing media from the extraction of rice husk ash using KOH 0,5M solvent. From the results of this study, the design of fire protection for silica gel-based kitchens made from rice husk ash is effectively used and easy to install in the kitchen area.